Student Learning Motivation - Muhammad Anas; Farida Aryani (Indonesian Journal of Educational Studies, 2017)
This study aimed to presents: (1) an overview of internal motivation to learn the behavior of students, both in following the lectures; (2) an overview of external motivation to study the behavior of students; (3) describe the picture of students' perceptions of the value obtained; (4) an overview of ways to earn graduate students. This study uses a quantitative approach to implementation is the way the survey. Locutions research, the Faculty of Education State University of Makassar. Sources of data in this study, student faculty of the State University of Makassar class education 2011-2012. Data collection techniques used are: questionnaire and documentation. Data analysis was performed in an interactive and continuous progress through to completion. Results showed motivation for attending is very large, and they have a huge desire to get a passing grade.